Application of mutation inspired constrained factor PSO considering voltage stability and losses by locating and rating TCSC during N-1 contingency. (2018) - Jayachitra, S.; Baskar, G.; Feridinand, T.
This paper describes, a strategy for optimal placement and setting of series FACTS controller thyristor controlled series capacitor (TCSC) under single line contingency (N-1) using particle swarm optimisation (PSO), constriction factor PSO (CFPSO), Cauchy mutation-CFPSO (CM-CFPSO) and Gaussian mutation-CFPSO (GM-CFPSO) algorithm in order to reduce over loading and power loss in transmission lines and to improve voltage stability of a power system. In this proposed CM-CFPSO and GM-CFPSO methods, a new-fangled position equation is framed and the features of the constriction factor approach (CF) is incorporated with the proposed approach. To detect the most severe transmission line, composite severity index (COSI) is calculated under N-1 contingency and top three severe lines are taken for this research work. To validate the consequence of proposed approach, simulation studies are carried out on a standard IEEE 30-bus network. Appraisals are made in provisions of eminence solution, execution time and stable convergence behaviour.